From Print to Cyberspace: The Trend toward Electronic Journals Presentation and Access Issues in a Medium-Sized Academic Institution - MacLennan, Birdie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
No Abstract Available.